DINAMIKA PERILAKU INDIVIDU GURU DAN DAMPAKNYA TERHADAP IKLIM ORGANISASI DI SMP NEGERI 3 AJIBARANG - Jati, Histura Priya; Suparjo, Suparjo (STKIP Pesisir Selatan, 2025)
This study focuses on analyzing the dynamics of teacher behavior and its influence on the organizational climate at SMP Negeri 3 Ajibarang. Variations in teacher behavior, including work motivation, discipline, communication skills, and adaptability to change, create significant differences in the implementation of tasks and daily interactions. This diversity not only impacts the effectiveness of cooperation between teachers but also shapes collective perceptions of the school's organizational climate. Using a qualitative approach through a case study design, this study was conducted through observation, in-depth interviews, and document analysis. These methods provide a comprehensive overview of work patterns, social interactions, and contextual factors that influence teacher behavior. The results indicate that positive behaviors, such as open communication, consistent discipline, and a willingness to cooperate, contribute to the creation of a harmonious, conducive, and productive organizational climate. Conversely, less adaptive behavior often creates obstacles in the coordination and implementation of school policies. Factors that encourage positive behavior include the principal's participatory leadership, a collaborative work culture, a clear organizational vision, and recognition of teacher performance.